Juventudes do campo: a construção de sujeitos sociopolíticos e a afirmação de direitos - Elis Medrado Viana (2017)
In this work, the rural youth takes part in a debate on the processes that lead to recognition of the central role young people have in community life and assertion of rights. This group seeks to be recognized as protagonists of their own history, opposing ideas that associate youth to a transitional stage of life. Particularly, rural youth must break paradigms that undervalue country practices in favor of urban groups. Education is one of the many categories used to set apart rural from urban youth. The lack of courses focused on peasant life and the low quality of education in the countryside are obstacles for young people to stay in their communities. Motivations for youth engagement and the analysis of their formative and transformative practices are approached here in a way that contributes to understanding rural youth as a social actor. Through observation of courses, meetings and events in Alto Rio Pardo, fieldwork, questionnaires and interviews, it was possible to analyze youth participation in the territory and in discussions about the youth, the rural and education. Within Alto Rio Pardo, the municipality of Rio Pardo de Minas stands out for numerous youth-led activities and large presence of young people in rural courses at the four Federal Universities in the state of Minas Gerais which offer them. In addition, the municipality maintains an Agricultural Family School, which is the locus of this research as it helps young people achieve sociopolitical recognition. The research has also shown how youth practices contribute to the defense of land rights and to ensuring their identity as traditional geraizeira communities. Youth engagement in social movements, as well as in peasant and community issues, have been creating new formative spaces, increasing the permanence of young people in rural areas through formative practices such as rural schools. Educational processes that lead to youth and community participation in the countryside are therefore increasingly encouraged and desired.